High-intensity laser application in Orthodontics - Sant’Anna,Eduardo Franzotti (2017)
ABSTRACT Introduction: In dental practice, low-level laser therapy (LLLT) and high-intensity laser therapy (HILT) are mainly used for dental surgery and biostimulation therapy. Within the Orthodontic specialty, while LLLT has been widely used to treat pain associated with orthodontic movement, accelerate bone regeneration after rapid maxillary expansion, and enhance orthodontic tooth movement, HILT, in turn, has been seen as an alternative for addressing soft tissue complications associated to orthodontic treatment. Objective: The aim of this study is to discuss HILT applications in orthodontic treatment. Methods: This study describes the use of HILT in surgical treatments such as gingivectomy, ulotomy, ulectomy, fiberotomy, labial and lingual frenectomies, as well as hard tissue and other dental restorative materials applications. Conclusion: Despite the many applications for lasers in Orthodontics, they are still underused by Brazilian practitioners. However, it is quite likely that this demand will increase over the next years - following the trend in the USA, where laser therapies are more widely used.